1999
DOI: 10.1016/s1097-2765(00)80346-9
|View full text |Cite
|
Sign up to set email alerts
|

MSH2 and MSH6 Are Required for Removal of Adenine Misincorporated Opposite 8-Oxo-Guanine in S. cerevisiae

Abstract: Oxidation of G in DNA yields 8-oxo-G (GO), a mutagenic lesion that leads to misincorporation of A opposite GO. In E. coli, GO in GO:C base pairs is removed by MutM, and A in GO:A mispairs is removed by MutY. In S. cerevisiae, mutations in MSH2 or MSH6 caused a synergistic increase in mutation rate in combination with mutations in OGG1, which encodes a MutM homolog, resulting in a 140- to 218-fold increase in the G:C-to-T:A transversion rate. Consistent with this, MSH2-MSH6 complex bound to GO:A mispairs and GO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
145
1
7

Year Published

2001
2001
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 210 publications
(166 citation statements)
references
References 34 publications
(5 reference statements)
13
145
1
7
Order By: Relevance
“…In particular, MMR recognizes the mismatches in heteroduplex recombination intermediates, preventing completion of recombination between diverged sequences, thus promoting genetic stability (42)(43)(44). More recently, several groups have shown that MMR is involved in the repair of mismatched 8-oxoguanine, which is one of the major base lesions formed after DNA oxidative attack (45), and may participate in the transcriptioncoupled repair pathway (46,47). Cells with a defective MMR show a mutation rate 100-fold greater than that of normal cells, causing the accumulation of potentially deleterious mutations throughout the genome.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, MMR recognizes the mismatches in heteroduplex recombination intermediates, preventing completion of recombination between diverged sequences, thus promoting genetic stability (42)(43)(44). More recently, several groups have shown that MMR is involved in the repair of mismatched 8-oxoguanine, which is one of the major base lesions formed after DNA oxidative attack (45), and may participate in the transcriptioncoupled repair pathway (46,47). Cells with a defective MMR show a mutation rate 100-fold greater than that of normal cells, causing the accumulation of potentially deleterious mutations throughout the genome.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, oxidative damage of DNA has been correlated with the ageing process. MutSα can target 8-oxo-guanine mispairs for repair (Mazurek et al, 2002;Ni et al, 1999), and treatment of HEL cells with H 2 O 2 is associated with a reduction in MMR and with decreased levels of some MMR proteins (see, e.g. Chang et al, 2002).…”
Section: Mmr and Ageingmentioning
confidence: 99%
“…In addition to correcting single base replication errors involving undamaged bases, several studies have shown that Msh6 (but not Msh3) also participates in correcting mismatches resulting from replication of 8-oxo-G, a common lesion generated by oxidative stress [33][34][35][36][37][38]. A signature of oxidative stress-induced substitutions is a G-C to T-A transversion, which results when dAMP is incorporated opposite 8-oxo-G in its syn conformation in the template strand [39].…”
Section: The Function Of Glu339 In Yeast Msh6mentioning
confidence: 99%